Pengaruh Keaktifan Taruna di Kelas Terhadap Nilai Mata Kuliah Dasar- Dasar Akuntansi - Sulida Erliyana; Iik Suryati Azizah; Evyana Diah Kusumawati (Majalah Ilmiah Bahari Jogja, 2020)
This study aims to find out (1) the relationship of active cadets in the classroom with the score of accounting basics courses in Polytechnic Bumi Akpelni and (2) the form of active cadets in the classroom during accounting basics courses. The population on this study is the KPN cadets of Polytechnic Bumi Akpelni. The data collection was carried out by using the questionnaire method. The trial of this instrument simple regression analysis was used and carried out by 60 cadets of the KPN study program. There are assumptions that it must be met in a regression analysis. These assumptions include normality, heteroscedasticity, multicollinearity and autocorrelation. The results of this study are: (1) There is a relationship between the activeness of cadets in the classroom and the score of accounting basics courses at the Polytechnic Bumi Akpelni. The score of accounting basics courses which influenced by the activeness of cadets in the classroom is 68.7%. While 31.3% is influenced by the other factor of outside this study. (2) The form of active cadets when learning the basics accounting includes asking about the material being taught and being active in solving problems given by the lecturer.